Amelioration of Beta Interferon Inhibition by NS4B Contributes to Attenuating Tembusu Virus Virulence in Ducks - Zhang, Wei; Zeng, Miao; Jiang, Bowen; Lu, Tong; Guo, Jiaqi; Hu, Tao; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; et al. (Frontiers in Immunology, 2021)
Our previous studies reported that duck Tembusu virus (DTMUV) nonstructural protein 2A (NS2A) is a major inhibitor of the IFNβ signaling pathway through competitively binding to STING with TBK1, leading to a reduction in TBK1 phosphorylation (Zhang, et al., J. Virol. 2020). DTMUV NS2B3 could cleave and bind STING to subvert the IFNβ signaling pathway (Wu, et al., J. Immunol. 2019). Here, we found that DTMUV NS4B competitively bound to STING with TBK1, reducing TBK1 phosphorylation and inhibiting the IFNβ signaling pathway by using the Dual-Glo® Luciferase Assay System and the NanoBiT protein-protein interaction (PPI) assay. We further identified the E2, M3, G4, W5, K10 and D34 residues in NS4B that were important for its interaction with STING and its inhibition of IFNβ induction, which were subsequently introduced into a DTMUV replicon and an infectious cDNA clone. We found that the NS4B M3A mutant enhanced RNA replication and exhibited significantly higher titer levels than WT at 48-72 hpi but significantly decreased mortality (80%) in duck embryos compared to WT (100%); the NS4B G4A and R36A mutants slightly reduced RNA replication but exhibited the same titer levels as WT. However, the NS4B R36A mutant did not attenuate the virulence in duck embryos, whereas the G4A mutant significantly decreased the mortality (70%) of duck embryos. In addition, the NS4B W5A mutant did not affect viral replication, whereas the D34A mutant slightly reduced RNA replication, and both mutants exhibited significantly lower titer levels than the WT and significantly decreased mortality (90% and 70%, respectively) in duck embryos. Hence, our findings provide new insight into the development of attenuated flaviviruses by targeting the disabling viral strategies used to evade the innate defense mechanisms.